Critical Thinking Skills Analysis of Chemistry Pre-service Teacher in Developing Chemistry-learning Tools Based on Islam-science Integration (Study at Department of Chemistry Education, Faculty of Science and Technology, UIN Sunan Kalijaga Yogyakarta) - Jamil Suprihatiningrum (Kaunia: Integration and Interconnection Islam and Science, 2016)
Critical thinking is the ability to think clearly and rationally about what to do or what to believe. It includes the ability to engage in reflective and independent thinking. This study aimed to determine the critical thinking skills of pre-service teachers of chemistry education department at Faculty of Science and Technology, UIN Sunan Kalijaga; what barriers are owned by the students to develop critical thinking skills in developing learning tools; and efforts to what can be done by the department to improve those critical thinking skills. This research is a descriptive study that carried out in several stages: the development of research instruments (analysis learning tools sheet, critical thinking skills scale, interview guides, FGD questions guide); research instruments validation; data collection; data analysis; as well as inference and reporting. Analysis of the learning tools compiled by the students shows that there were weaknesses in determining student learning outcomes, which was found 60% selection of the type of assessment does not match with the learning objectives. Critical thinking skills of students are at a good level with an average ideal percentage of 72.7%. The lowest score obtained in “advanced clarification“ aspect, which was also proved from the interviews, the students did not have enough knowledge to explain more detail what was said previously. FGD with professors indicated that the necessary coordination meeting between lecturer at the beginning of each semester so that the distribution of matter in all subjects do not overlap.